Embracing the digital revolution: exploring the acceptance and potential of artificial intelligence in physiotherapy - K. B., Riyas Basheer; Bills, Anusha (International Journal of Research in Medical Sciences, 2024)
Recently, there has been significant discussion about artificial intelligence (AI) and Large Language Models (LLMs) as they relate to teaching and learning. To date, literature exists about the role of AI in Physical Therapy treatment, but not Physical Therapy education. This review will identify the benefits of adapting AI into Physical Therapy education to better prepare the healthcare providers of tomorrow. Survey research shows that AI can improve access to information, increase productivity, and reduce errors. However, most also feel ill-informed on the topic. A majority agreed that AI concepts should be included in Physical Therapy education. While valid concerns exist about AI sources giving false information, as well as the potential to use these services to plagiarize work, tools are already in existence to mitigate these issues. Potential benefits of AI in physical therapy education include the ability to produce examples, provide different explanations, and assist in assessing student learning while providing immediate feedback on performance. With the scope of AI rapidly expanding, we believe it is imperative for physical therapy educators to have access to current information about its potential benefits, uses, and limitations. While many professionals do not currently possess much knowledge on the topic, there is a growing consensus as to the role it will play in our profession in the future. While discussions of AI can raise more questions than answers, preparation now will reduce the need for urgent adaptations in the future.